PenseSUS e as redes sociais: a busca por estratégias de comunicação e os desafios para a democratização e descentralização do debate sobre o SUS (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
PenseSUS and social networks: the search for communication strategies and the challenges for the democratization and decentralization of the debate on SUS